Nanoparticle-induced systemic toxicity and immune response in Galleria mellonella larvae - Payoe, Kusal Shasheen; Gadar, Kavita; Flahaut, Emmanuel; McCarthy, Ronan R.; Stenbeck, Gudrun (Frontiers in Pharmacology, 2025)
IntroductionNanotechnology is one of the most rapidly advancing scientific fields, offering innovative solutions in diverse areas such as medicine, agriculture, and materials science. However, concerns regarding the environmental and biological toxicity of nanomaterials continue to rise. It is thus essential to develop reliable, ethical, and cost-effective models to assess the in vivo toxicity of Nanoparticles (NPs). This study aims to evaluate the immunotoxicity and systemic effects of various inorganic nanoparticles using Galleria mellonella (GM) larvae as a non-mammalian in vivo model.MethodsGM larvae were exposed to different types of NPs, including starch-coated and anionic superparamagnetic iron oxide nanoparticles (SPIONs), double-walled carbon nanotubes (CNTs), and gold nanoparticles (GNPs). Flow cytometry was used to monitor haemocyte numbers, while larval survival assays assessed mortality. Histological analyses were conducted to detect CNT accumulation in tissues. The immunosuppressive effects of GNPs were assessed in GM larvae challenged with sub-lethal doses of Pseudomonas aeruginosa and Acinetobacter baumannii.ResultsThe results demonstrate NP retention in GM tissues and showed that surface and size properties of NPs significantly influenced their biological effects. Anionic SPIONs lacking a starch coating caused greater haemocyte depletion and higher mortality than their biocompatible coated counterparts. GNP toxicity was found to be size‐dependent, with particles between 60 and 100 nm producing the most severe haemocyte depletion, which was comparable to that obtained with the immune suppressant cyclophosphamide.ConclusionOverall, this study supports the use of GM larvae as an effective model for nanoparticle toxicity screening and demonstrates the usefulness of this model in detecting both toxic and immunosuppressive properties of nanomaterials.